Study of Intracellular Peptides of the Central Nervous System of Zebrafish (Danio rerio) in a Parkinson’s Disease Model - Fiametti, Louise O. [UNESP]; Franco, Camilla A. [UNESP]; Nunes, Leticia O. C. [UNESP]; de Castro, Leandro M. [UNESP]; Santos-Filho, Norival A. [UNESP] (MDPI, 2025)
Although peptides have been shown to have biological functions in neurodegenerative diseases, their role in Parkinson’s disease has been understudied. A previous study by our group, which used a 6-hydroxydopamine zebrafish model, suggested that nine intracellular peptides may play a part in this condition. In this context, our aim is to better understand the role of five of these nine peptides. The selection of peptides was made based on their precursor proteins, which are fatty acid binding protein 7, mitochondrial ribosomal protein S36, MARCKS-related protein 1-B, excitatory amino acid transporter 2 and thymosin beta-4. The peptides were chemically synthesized in solid phase and characterized by high-performance liquid chromatography and mass spectrometry. Circular dichroism was performed to determine the secondary structure of each peptide, which showed that all five peptides maintain a random structure in the aqueous solutions that were studied. Two molecules show a helical profile in trifluoroethanol, a known structuring agent. Cell viability by the MTT assay indicates that all five peptides are not cytotoxic in all concentrations tested in both mouse and human cell lines. Behavioral assay using a 6-OHDA zebrafish larvae model suggest that all peptides help in the recovery of motor function with 24 h treatment at two concentrations. Three peptides showed a complete recovery from the 6-OHDA-induced motor impairment. Further studies are needed to better understand the mechanism of action of these peptides and whether they are truly a potential ally against Parkinson’s disease.
Keywords: intracellular peptides; Parkinson’s disease; zebrafish larvae